Cytokine Signatures in Mucocutaneous and Ocular Behçet’s Disease - Lopalco, Giuseppe; Lucherini, Orso Maria; Lopalco, Antonio; Venerito, Vincenzo; Fabiani, Claudia; Frediani, Bruno; Galeazzi, Mauro; Lapadula, Giovanni; Cantarini, Luca; Iannone, Florenzo (Frontiers in Immunology, 2017)
Behçet's disease (BD) is a multi-systemic inflammatory disorder consisting of recurrent oral aph-thosis, genital ulcers, and chronic relapsing bilateral uveitis, however many other organs may be affected. Several pro-inflammatory cytokines, mainly derived from Th1 and Th17 lymphocytes, seem to be involved in different pathogenic pathways leading to development of the clinical manifestations. On this basis, the primary aim of our study was to compare a core set of proin-flammatory cytokines between patients with BD and healthy control (HC). The secondary goal was to evaluate potential correlations between these putative circulating biomarkers, the status of disease activity, and the specific organ involvement at the time of sample collection. Fifty-four serum samples were collected from 46 BD patients (17 males, 29 females, mean age 45,5 ± 11,3 years), and 19 HC (10 males, 9 females, mean age 43 ± 8.3 years). Twenty-five se-rum cytokines (APRIL/TNFS13, BAFF/TNFSF13B, sCD30/TNFRSF8, sCD163, Chitinase3-like1, gp130/sIL-6Rb, IFNb, sIL-6Ra, IL-10, IL-11, IL-19, IL-20, IL-26, IL-27 (p28), IL-28A/IFN-lambda2, IL-29/IFN-lambda1, IL-32, IL-34, IL-35, LIGHT/TNFSF-14, Pentraxin-3, sTNF-R1, sTNF-R2, TSLP and TWEAK/TNFSF-12) were simultaneously quantified using a Bio-Rad cytokine bead arrays. Serum concentration of sTNF-R1 (p<0.01) and sTNF-R2 (p<0.01) resulted higher in both active- and inactive-BD than HC, whilst Chitinase3-like1 (p<0.05) and gp130/sIL-6Rb (p<0.01) serum levels were significantly higher in inactive-BD, and IL-26 (p<0.01) in active-BD than HC. No differences were observed between inactive- and active- BD group. In addition, we observed that gp130/sIL-6Rb, sIL-6Ra, IL-35, and TSLP serum levels were significantly enhanced in pa-tients with mucocutenous manifestations plus ocular involvement (MO-BD) compared to sub-group with only mucocutaneous involvement (M-BD). Our findings may suggest a signature of IL-6, TNF-α as well as of Th17 response in BD patients due to increased levels of gp130/sIL-6Rb, sTNF-R1, sTNF-R2, IL-26 respectively. This evidence could contribute to improve the knowledge regarding the role of these citokines in the induction of specific BD clinical features.